RESEARCH ON DYNAMIC RESPONSE WITH CRASHWORTHY DEVICES OF OFFSHORE WIND TURBINE FUNDATION TO SHIP IMPACT - HAN ZhiWei; LI Chun; ZHOU HongJie; DING QinWei; YU Wan (Jixie qiangdu)
The probability of collisions between offshore wind turbines and ships increases with the development of offshore wind farm. Based on nonlinear dynamic analysis method,through LS-DYNA to simulate the 5000 t ship impact a 4 MW offshore wind turbine tripod at different speed,study rubber-foam aluminum-steel crashworthy devices influence on structure dynamic response characteristics of tower in the process of collision. Comparison and analysis of energy conversion,maximum collision force and stress distribution at the collision between offshore wind turbine and ship collision system with or without guard. The results show that the top of the tower of wind turbine response inhibition effect is obvious after the installation of crashworthy devices; The biggest displacement,velocity and acceleration of top tower than the absence of protective device decreased by 56. 4%,27. 2% and 44. 2% respectively; Tower bottom structure deformation can be dramatically reduced,deep of tower less than the uncrashworthy devices; Crashworthy devices to avoid the collision force focused on tower,to a certain extent,reduce the concentration of stress.